Penegakan Hukum Terhadap Pelanggaran Muatan Angkutan Barang Di Jalan Kabupaten (Studi Di Kabupaten Langkat) - Tarigan, Harimin; Jauhari, Iman; Sikumbang, Jusmadi (Universitas Medan Area, 2020)
This research aims to analyze the factors that cause the violation regulation of the charge transport of goods, to see the implementation of traffic and transportation laws which regulate the rule of the charge transport of goods and to review the exertions that can be done in law enforcement to the violation regulation of the charge transport of goods on the road of district. This research is the research of sociolegal law using the combination of normative juridical and empirical juridical method which having descriptive characteristic and perspective form. After analyzing the data, noted that the factors of the violation regulation of the charge transport of goods on the road of district: 1) the law substance, the legislation of traffic and transportation has not clearly organized the system of punishment for the offender of the violation regulation of the charge transport of goods on the road of district; 2) the law structure, the low quality and quantity of law upholder and also the low quality and quantity of law enforcement’s tools and facilities; 3) the law culture, the low level of work motivation, low commitment and low moral integrity of law upholder, along with the public’s obedience and knowledge about the determinate regulation of the charge transport of goods. The implementation of laws which controls the certain regulation of the charge transport of goods on the road of district is not done optimally by the inhabitants, the law culture of society and law upholder. The exertions that can be done as the law enforcement of the regulation of the charge transport of goods on the road of district are in preemptive way or using punishment, in preventive way and repressive way or using punishment tools.